2016
DOI: 10.4172/2157-7625.1000207
|View full text |Cite
|
Sign up to set email alerts
|

Sandfly and Leishmaniasis: A Review

Abstract: Sandfly has a long history of association with humans, which still are suffering from its harmful impacts. It parasites humans and other animals and acts as a source of nuisance and annoyance to them. The present bibliographical study explains the role of Sandfly as a disease vector of Leishmaniasis. This article highlights various aspects of the life of the vector which includes its general description of morphology, biology, life cycle, and major control strategies. Regarding to control strategies of the vec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
1
8
0
1
Order By: Relevance
“…Therefore, travelling spread leishmaniasis in people which are living in non-endemic areas. 36 In general, this study indicated the transmission hotspot districts in Wag Hemra zone, Northeast Ethiopia over time from 2016 to 2020. Mapping of CL risk areas could be useful to identify priority regions or areas to establish CL diagnostic and treatment services, to conduct clinical trials and take prevention and control measures in these areas.…”
Section: Discussionmentioning
confidence: 59%
“…Therefore, travelling spread leishmaniasis in people which are living in non-endemic areas. 36 In general, this study indicated the transmission hotspot districts in Wag Hemra zone, Northeast Ethiopia over time from 2016 to 2020. Mapping of CL risk areas could be useful to identify priority regions or areas to establish CL diagnostic and treatment services, to conduct clinical trials and take prevention and control measures in these areas.…”
Section: Discussionmentioning
confidence: 59%
“…Our results support these findings as our model shows that sandflies that occupy areas with lower human modification and higher land integrity are more likely to be vectors. Since the opposite is true for the effect of human modification on reservoir host communities, this may indicate that the highest risk of Leishmania spillover lies at the interface between human modification and intact forests [95]. Indeed, synanthropic sandfly species that live in domestic habitats, but are associated with higher-integrity land cover, were more likely to be vectors.…”
Section: Discussionmentioning
confidence: 99%
“…The Leishmaniases are caused by parasitic protozoa of the genus Leishmania and are transmitted via the bite of infected female phlebotomine sand flies. Clinical forms range from self-healing but disfiguring cutaneous (CL) and mucocutaneous forms (MCL) [1][2][3] to potentially fatal visceral leishmaniasis (VL) [2], which can also lead to post-kala-azar dermal leishmaniasis (PKDL) in some instances following treatment [4]. No vaccine against human leishmaniasis exists [5], and patient management relies on chemotherapy, which is currently unsatisfactory for reasons including cost, toxicity [6,7], duration and mode of administration and drug resistance [1,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%